Анализа на кризната состојба и справувањето со пожарите во Република Северна Македонија низ призма на функционалноста на системот за управување со кризи и заштита и спасување -Студија на случај - GJurovski, Marjan; Малиш Саздовска, Марина; Смилески, Росе; Моцаноски, Менде (Универзитет, Св. Климент Охридски'' - Битола Факултет за безбедност - Скопје, 2022)
Subject of research With the trend of scientific, technical, and technological achievements, especially in the last few decades, one gets the impression that complex situations have arisen in our lives. Certain conditions cannot be typified or studied without a systematic approach to the problem. Fires and explosions are a potential danger to the health and life of people, animals, properties, the environment, and they cause material damage. Often in practice, some people intentionally set fires or cause an explosion while committing a crime or to cover up a crime that has already been committed. The processes of burning, the fires, and explosions, in the scientific sense, are constantly the subject of research. The scientific approach to the investigation of fires and explosions imposes the need for in-depth knowledge of the theory of combustion processes, the processes of uncontrolled burning - fires, extinguishing tactics, criminalistic-criminological sciences, as well as other scientific disciplines. Objective of the project The purpose of the case analysis is to determine the functionality of the system for crisis management and protection and rescue in conditions of declared crisis when dealing with fires and to carry out a scientific description of the investigation of the occurred fires. The research in a practical sense aims to get, among other things, the data, and the factual situation about the conditions in which the competent authorities work into the causes of fires and explosions. Within the text, the foreign experiences related to the subject of the research of this paper, which are applicable to the specific conditions in the Republic of North Macedonia, are presented and transferred. Mission of the case analysis The authors analyze the layout and functionality of the current concept for crisis management and the concept for protection and rescue of the Republic of North Macedonia during firefighting when a state of crisis was declared and on two other bases, that is, a rapid basis of risks and threats in order to come to proposals and possible solutions for building an efficient security system where crisis management and protection and rescue in the Republic of North Macedonia are an integral part, and of course the creation of an appropriate security policy. The security system of the Republic of North Macedonia has prevention in its tasks in the context of reducing the risks of pandemics and natural disasters and unifying the preventive activities of all institutions involved with the crisis management system and the protection and rescue system. 6 Tasks The main task faced by the authors is to review the current approaches in the prevention and handling of fires as a disaster by the nature and humans, with a special emphasis on the plans for a crisis and continuation of the work, covered through the case study and analysis of the response of the institutions. At the same time, the degree of coordination, as well as the inter-departmental and inter-institutional cooperation of all involved in the security system was determined, where the crisis management system is an integral part, which is organized and maintained for the purpose of prevention, early warning and dealing with crises that pose a risk to goods, health and life of people and animals and which directly threaten safety. A better understanding of the nature of planning for prevention and dealing with disasters in building capacities at the local and national level in the Republic of North Macedonia and in developed countries and within international organizations is closely related to crisis management. Among other things, the possibilities and limitations of tools and approaches in the creation and implementation of the plan for crisis situations and continuation of work, at different levels, were explored. How to achieve a holistic approach in crisis management at the local, regional, European and world level, based on inter-agency and international cooperation between the civilian and military components of the crisis management system. Scientific and practical goals that were realized through the case analysis, i.e., the project: • Determination of the basic factors and their influence on the successful implementation of the concept of protection and rescue, that is, crisis management in a crisis. • Which of the basic crisis management concepts are the most suitable and applicable in the security system of the Republic of North Macedonia. • Possible critical areas in the security system of the Republic of North Macedonia were determined, in which elements are needed for a positive change in crisis management and protection and rescue for daily functioning in crisis conditions. • The perception and interpretation of the approach of our country in the field of crisis management, which offers data based on which the shortcomings and omissions in the action on a strategic and operational level will be determined. • With the help of the results obtained from the research methods and techniques, the points that represent a kind of "brake" in the communication and cooperation of the relevant actors in the system were identified. 7 • Recommendations were made on understanding disaster risks; strengthening disaster risk management; investing in disaster risk reduction; readiness for an efficient response in the process of recovery, rehabilitation, and reconstruction. • Developing early warning systems for fires and other disasters. The topic cover types of early warning systems, stages of development (including a comparative presentation of the terminologically different, but essentially similar systems) and their overall effectiveness at the state and local level. • Planning crisis situations. In addition to theories and approaches, it is envisaged to deal with contents related to the planning process, developing a scenario, developing a plan for emergency and crisis situations and management within the plan.
Keywords: fires, crises, protection and rescue